Aplikasi Penyimpan Koordinat Lokasi Beserta Rute dan Tracking Map Berbasis Mobile Android - Kamal Fadl-Lu Maulayal Matin; Slamet Sugiarto; Happy Chrismana Datu (Universitas Darussalam Gontor, 2016)
The quickly and accurately access to information has become the society necessary in the 21st century. The information in this period not only presented in the form of verbal communication, technological developments have enabled some information at once can be wrapped in a visual minimalist form. One popular technology is Google Map. Despite the existence of Google Map has helped many people to facilitate access to the full location, but in term of usage, society tends to only require information related to everyday life. Therefore, the ability of more suitable minimalist information to facilitate the publicin performing daily activities. We create an application that can provide location information that specifically aims to facilitate the public in performing daily activities. The application work using GPS technology-based Google APIs and runs on the Android platform. The information presented depends on the activities of daily users, either in the form of the most frequently visited locations, routes oftravel, location tracking, and navigation. All locations will be stored in the database of SaveLoc application, sso that the information that has been stored can be accessed anytime and anywhere.